## Smart Fallacies: i=1, 1= 2 and 1= 3

This mathematical fallacy is due to a simple assumption, that $ -1=\dfrac{-1}{1}=\dfrac{1}{-1}$ . Proceeding with $ \dfrac{-1}{1}=\dfrac{1}{-1}$ and taking square-roots of both sides, we get: $ \dfrac{\sqrt{-1}}{\sqrt{1}}=\dfrac{\sqrt{1}}{\sqrt{-1}}$ Now, as the Euler's constant $ i= \sqrt{-1}$…

Kalpana:wao great post.. m boring with my old style blog..…view comment →

vani:Amazing sites which you have listed in this post. You…view comment →

Make Up Artist Melbourne:Great post. Awesome work for the makeup artist. Thank you…view comment →

Gaurav Tiwari:Yes, you are right. I missed the symbol. Fixed.view comment →

Anirban Kopty:Sir, I think the eqⁿ 1 needs to be corrected!…view comment →